Examining the impact of globalization in the environmental Kuznets curve hypothesis: the case of tourist destination states - Akadiri, Seyi Saint; Lasisi, Taiwo Temitope; Uzuner, Gizem; Akadiri, Ada Chigozie (Springer Heidelberg, 2019)
This paper examines the relationship between carbon emissions and international tourism growth through the channels of globalization, energy consumption, and real income via testing the environmental Kuznets curve over the periods of 1995 to 2014 for 15 selected tourism destination states that prioritized tourism as a means of maximizing economic growth. Using the panel data analysis, results confirm globalization-tourism-induced EKC hypothesis for tourist destination states. This implies international tourism growth and carbon emissions, through the channels of energy consumption, globalization, and real income, are in a long-term equilibrium relationship. International tourism and squared term of real income have an inverse significant effect on carbon emission level, while energy consumption, globalization, and real income without squared term exert positive and significant effects on carbon emission level in the long-run. Thus, globalization-tourism-induced EKC hypothesis is suggested with credible policy suggestions in the case of tourist destination states.
Keywords: Tourism; Globalization; Economic growth; Carbon emissions; Energy consumption; Tourist destination states; C23; O40